2023
DOI: 10.1063/5.0166243
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on lock-in vortex-induced vibration of an airfoil at a high angle of attack based on detached eddy simulation

Bo Lian,
Xin Tong,
Xiaocheng Zhu
et al.

Abstract: Large-scale modern wind turbines at standstill are prone to vortex-induced vibration (VIV). In this study, coupled fluid–solid dynamics of the wind turbine airfoil at a 90° attack angle are performed using the detached eddy simulation. The fully developed vibration responses with different structural dampings are explored in detail. The frequency lock-in regime is determined, and the corresponding phase differences between the lift and displacement are presented with the Lissajous curve. The dominant surface p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…The results obtained are shown in Table 2, along with some values obtained for similar cases from the existing literature, all with the same airfoil. The Strouhal number for the 2D case is 0.126, which is in line with previously reported values for the same airfoil and with URANS, namely 0.125 by [9], 0.121 [13] by and 0.119 by [10]. The Strouhal number for the 3D1c case is 0.132, which is somewhat far from previously reported values for the same airfoil, namely 0.153 by [9] with DDES, and also 0.153 by [10] with DES.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The results obtained are shown in Table 2, along with some values obtained for similar cases from the existing literature, all with the same airfoil. The Strouhal number for the 2D case is 0.126, which is in line with previously reported values for the same airfoil and with URANS, namely 0.125 by [9], 0.121 [13] by and 0.119 by [10]. The Strouhal number for the 3D1c case is 0.132, which is somewhat far from previously reported values for the same airfoil, namely 0.153 by [9] with DDES, and also 0.153 by [10] with DES.…”
Section: Resultssupporting
confidence: 91%
“…The Strouhal number for the 2D case is 0.126, which is in line with previously reported values for the same airfoil and with URANS, namely 0.125 by [9], 0.121 [13] by and 0.119 by [10]. The Strouhal number for the 3D1c case is 0.132, which is somewhat far from previously reported values for the same airfoil, namely 0.153 by [9] with DDES, and also 0.153 by [10] with DES. The authors have found that for the 3D1c case there is a large uncertainty regarding the definition of the 5 Strouhal number, due to the presence of intermittent flow states with different vortex shedding frequencies.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations